4 - Interfacing the State and the Voluntary Sector for African Development: Lessons from Kenya - Wanyama, Fredrick O. (Africa Development, 2006)
The purpose of this paper is to examine the possibility of forging a complemen- tary role between the state and the voluntary sector as an alternative framework for enhancing African development, given that none of these actors have proved effective on their own. Using a study of community-based organisations (CBOs) – as a component part of the voluntary sector – in Western Kenya, it is argued that though these organisations have been instrumental in providing services that the state has been unable to provide, their effectiveness has been impeded by some deficiencies. It is pointed out that such deficiencies in CBOs should form the basis for bringing back the state in the development process and have it forge synergies with these organisations rather than co-opting them into its machinery, as has been the case in the past.